Answer:
See Explanation
Step-by-step explanation:
![log(x + y) = log3 + \frac{1}{2} logx+ \frac{1}{2} logy \\ \\ log(x + y) = log3 + logx ^{\frac{1}{2}} + logy ^{\frac{1}{2}}\\ \\ log(x + y) = log3 + log(xy) ^{\frac{1}{2}} \\ \\ log(x + y) = log[3(xy) ^{\frac{1}{2}}] \\ \\ x + y = 3(xy) ^{\frac{1}{2}} \\ \\ squaring \: both \: sides \\ {(x + y)}^{2} = \bigg(3(xy) ^{\frac{1}{2}} \bigg)^{2} \\ \\ {x}^{2} + {y}^{2} + 2xy = 9xy \\ \\ {x}^{2} + {y}^{2} = 9xy - 2xy \\ \\ \purple{ \bold{{x}^{2} + {y}^{2} = 7xy}} \\ thus \: proved](https://tex.z-dn.net/?f=log%28x%20%2B%20y%29%20%3D%20log3%20%2B%20%20%5Cfrac%7B1%7D%7B2%7D%20logx%2B%20%20%5Cfrac%7B1%7D%7B2%7D%20logy%20%5C%5C%20%20%5C%5C%20log%28x%20%2B%20y%29%20%3D%20log3%20%2B%20%20%20%20logx%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%20%2B%20%20%20logy%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%5C%5C%20%20%5C%5C%20%20log%28x%20%2B%20y%29%20%3D%20log3%20%2B%20%20%20%20log%28xy%29%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%20%5C%5C%20%20%5C%5C%20log%28x%20%2B%20y%29%20%3D%20%20log%5B3%28xy%29%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%5D%20%5C%5C%20%20%5C%5C%20x%20%2B%20y%20%3D%203%28xy%29%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%20%5C%5C%20%20%5C%5C%20squaring%20%5C%3A%20both%20%5C%3A%20sides%20%5C%5C%20%20%7B%28x%20%2B%20y%29%7D%5E%7B2%7D%20%20%3D%20%20%5Cbigg%283%28xy%29%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%20%5Cbigg%29%5E%7B2%7D%20%20%5C%5C%20%20%5C%5C%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20%2B%202xy%20%3D%209xy%20%5C%5C%20%20%5C%5C%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20%3D%209xy%20-%202xy%20%5C%5C%20%20%5C%5C%20%20%20%5Cpurple%7B%20%5Cbold%7B%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20%3D%207xy%7D%7D%20%5C%5C%20thus%20%5C%3A%20proved)
Answer:
Area = length x width
Area = (3width - 13) x width
Area = 3 width^2 -13width
56 = 3width^2 -13 width
Width = 7
Length = (3 *7) -13 = 8
Step-by-step explanation:
Answer:
(f + g)(x) = 5x - 3
Step-by-step explanation:
(f + g)(x)
= f(x) + g(x)
= 2x + 4 + 3x - 7 ← collect like terms
= 5x - 3
Answer:b. 0.22
Step-by-step explanation:
Since the lengths of adult walleye fishes are normally distributed, we would apply the formula for normal distribution which is expressed as
z = (x - µ)/σ
Where
x = lengths of walleye fishes.
µ = mean length
σ = standard deviation
From the information given,
µ = 44 cm
σ = 4 cm
We want to find the probability or fraction of fishes that are greater than 41 cm in length. It is expressed as
P(x > 41) = 1 - P(x ≤ 41)
For x = 41,
z = (41 - 44)/4 = - 0.75
Looking at the normal distribution table, the probability corresponding to the z score is 0.22